Evaluasi Konsentrasi Hormon Progresteron Pada Lobster (Panulirus versicolor) Dengan Ukuran Berbeda Menggunakan Metode Enzyme-Linked Immunosorbent Assay (ELISA) - Matakupan, Jolen; Sahetapy, Jacqueline M. F.; Louhenapessy, Daniel G.; Luturmas, Absalom; Palinussa, Elizabeth M. (Indonesian Journal of Sustainable Aquaculture, 2024)
Control of gonad maturation and spawning is a major problem in the development of shrimp and lobster cultivation. Reproductive technology in hatching this type of crustacean has not experienced significant development. Progesterone is a precursor of estrogen in vertebrates, which is also found in crustaceans and other invertebrates. While several crustacean reproductive hormones have been characterized, the identity and function of other reproductive hormones are still under investigation. In hormone analysis, the use of the Enzyme Linked Immunosorbent Assay (ELISA) method continues to grow, both for research purposes and clinical applications. This study aims to evaluate the concentration of the hormone progesterone in Panulirus versicolor lobsters of different sizes with a body weight range of 300-750g which are caught in the wild using the ELISA method. The hormone progesterone is measured in the ovaries, hepatopancreas and hemolymph. This research uses descriptive analysis methods. From using the ELISA method, the results of the parallelism test showed that the test sample curve was parallel to the standard curve. Absorbance and standard value recovery tests showed that the measured concentrations of the progesterone hormone in Panulirus versicolor lobsters were acceptable because they had an average recovery value of 98%. The precision testing results of the ELISA kit used show that the test prescription is good and acceptable based on the percentage of coefficient variation (%CV) from QC1 and QC 2 (<15%). The concentration value of the progesterone hormone in P. versicolor lobsters shows that there is a difference in concentration depending on body size, where in lobsters with a body weight of 650-750g, the concentration of the progesterone hormone in the hepatopancreas, ovaries and hemolin is 1.059 ng/ml, 0.357 ng/ml and 0.042 ng/ml. while at lower body weights, namely 300-350 grams, the concentration of the hormone progesterone is 0.753 ng/ml, 0.181 ng/ml, 0.010 ng/ml.